Complete mitochondrial genome of Tribolium castaneum (Coleoptera: Tenebrionidae) reared on sauce-flavor Daqu - Zhang, Xiaomeng; Huang, Rujia; Chen, Yubin; Li, Wang; Zhang, Xueqing; Yang, Jianghao; Lv, Jun (Frontiers in Insect Science, 2025)
The red flour beetle Tribolium castaneum (Coleoptera: Tenebrionidae), a cosmopolitan stored-product pest frequently infesting sauce-flavor Daqu (a multi-microbial fermented starter), may experience mitochondrial genome variations under the selective pressure exerted by this enzyme-rich substrate. Here we test whether feeding on sauce-flavor Daqu is associated with mitogenomic differences in T. castaneum. We present the complete mitochondrial genome of T. castaneum from this environment: a 15,885 bp circular DNA (GenBank PV563855) retaining ancestral insect architecture with 71.81% A+T content and slight positive AT skew. The genome contains 37 functional elements: 22 tRNA genes (all exhibiting atypical cloverleaf structures except trnS1(AGN)), 13 protein-coding genes (PCGs), 2 rRNA genes, and a 1,238 bp A+T-rich control region (82.80% AT). Eleven PCGs initiate with ATN codons, while cox1 (CTG) and nad1 (TTG) show divergent initiation. Ten PCGs terminate with TAA/TAG codons. Gene order aligns with basal insect mitogenomes. Comparative analysis with Jiangsu (China) and California (USA) strains revealed conserved structural features, though sequence/assembly discrepancies require further investigation to assess potential pressure-induced mutations. While these differences may reflect adaptations to the enzyme-rich Daqu environment, technical and geographical factors could also contribute; further functional studies are needed to establish causal links.